OP43 Financial strain modifies the association between systemic inflammation and cardiovascular mortality. (September 2018) - Lassale, C; Lazzarino, AI
Abstract : Background: Atherosclerosis and cardiovascular disease (CVD) have an inflammatory origin. Moreover, chronic psychosocial stress is associated both with inflammation and CVD. Our aim was to test whether the prognostic value for future CVD risk of a single inflammation test depends on the presence of chronic psychosocial stress. Methods: Data come from the nationally-representative English Longitudinal Study of Ageing. Psychosocial factors (financial strain, depression, social isolation, loneliness) and inflammatory markers (serum fibrinogen and C-reactive protein [CRP]) were collected in 4762 men and women, free of CVD and aged 52 to 101 y at baseline (2004–2005). Cox proportional hazards regression models were fitted to estimate the relationship (hazard ratios [HR] and 95% confidence intervals) between inflammatory marker and incident CVD death. Interactions terms between fibrinogen and each psychosocial factor were tested. Models were stratified by sex and adjusted for age, smoking, body mass index, physical activity, HDL/total cholesterol, triglycerides, hypertension and diabetes. Added predictive value over conventional CVD risk factors was assessed by change in C-statistics and reclassification. Results: There were 158 CVD deaths during a median follow-up of 8.1 y. The association between both inflammatory markers and CVD mortality was linear: HR 1 g/L of fibrinogen=1.46; 95% CI 1.20, 1.78 and HR log-unit CRP=1.35; 1.16, 1.57. Financial strain modified these associations. In the presence of financial strain (n=506, 24 deaths), the HRs for fibrinogen (3.32; 1.68, 6.57) and for CRP (2.15; 1.42, 3.26) were stronger than in the absence of financial strain (n=4256, 134 deaths) (HR fibrinogen 1.33; 1.07, 1.66 and HR CRP 1.26; 1.07, 1.49). The added predictive value was higher in the group that experienced financial strain, in particular for CRP. Conclusion: The positive association between inflammatory biomarkers and CVD death was much stronger in the presence of financial strain. When assessing the presence of inflammation with a single test for prediction of CVD risk, it may be necessary to take into account the presence of chronic psychosocial stress.